RESILIENSI ARSITEKTUR MASJID PASCA-BENCANA : KAJIAN PERAN MASJID SEBAGAI PUSAT MITIGASI BENCANA DI KOTA PALU - Hariyadi Salenda; Munarsi M; Sutrati Melissa Malik; Luthfiah; Irfandi; M. Rachmat Syahrullah Syahrullah (Teknosia, 2025)
Palu City is one of the areas with a high level of disaster risk, particularly earthquakes, tsunamis, and liquefaction. The disaster on September 28, 2018, revealed that mosques, besides functioning as places of worship, also play a crucial role in social life and serve as emergency shelters. This study aims to examine the potential of mosques as disaster mitigation centers by assessing community emotional attachment, accessibility, supporting facilities, as well as building design and safety. A mixed-method approach was employed through in-depth interviews and Likert-scale surveys with six respondents who were survivors sheltered in the Baiturrahim Grand Mosque, Palu. The findings indicate that the community’s social and emotional attachment to mosques is very strong, yet significant weaknesses remain in emergency facilities and evacuation signage. Meanwhile, the mosque structure is perceived as relatively strong and ready to serve as a temporary shelter. These results highlight the importance of strengthening the technical capacity of mosques through the provision of emergency facilities, basic logistics, and clear information systems, so that their role as disaster mitigation centers can be more effective in the future.